(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the current distribution and structure of pharmaceutical human resources at provincial traditional medicine hospitals nationwide. Subjects and Methods: A cross-sectional study was conducted on 799 pharmacy staff at 55 provincial traditional medicine hospitals as of December 31, 2022. Results: Postgraduate pharmacists (DSSĐH) account for 11.76%; university pharmacists (DSĐH) for 31.04%; intermediate and college-level pharmacists (DCĐ&TCD) for 53.94%; and assistant pharmacists (DT) for 3.25%. There is an imbalance in the structure of pharmaceutical human resources between urban and rural areas and within provinces. The ratios of pharmacists to intermediate and college-level pharmacists (DS/DCĐ&TCD), pharmacists to doctors (DS/ BS), and pharmacists to beds (DS/GB) are all low compared to the standards set by Circular 03/2023/TT-BYT. The distribution of pharmaceutical staff in traditional medicine hospitals is also uneven among provinces, with an average of only 6.2 pharmacists per hospital. Conclusion: There is a persistent imbalance in the structure of pharmaceutical human resources in traditional medicine hospitals between urban and rural regions across the country. The ratios of pharmacists to beds, doctors, and hospitals are below the standards of Circular 32/2020/TTBYT